Commerce and monetary systems in the ancient world : means of transmission and cultural interaction : proceedings of the fifth annual symposium of the Assyrian and Babylonian intellectual heritage project held in Innsbruck, Austria, October 3rd-8th 2002 (Stuttgart)
561 s.